2005
DOI: 10.1094/phyto-95-0659
|View full text |Cite
|
Sign up to set email alerts
|

Ceratothripoides claratris, a New Vector of a Capsicum chlorosis virus Isolate Infecting Tomato in Thailand

Abstract: Ceratothripoides claratris, the predominant thrips species on tomato in Thailand, was tested for vector competence and efficiency to transmit Capsicum chlorosis virus (CaCV) (isolate AIT) to tomato. The efficiency of adult-stage transmission was influenced by the larval stage at which virus was acquired. Adult C. claratris showed 69% transmission efficiency after acquiring the virus as freshly emerged (<1 h) first-instar larvae. However, when just molted (<1 h) second-instar larvae acquired the virus, the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Comparison of the N gene sequences of the WSMoV serogroup of tospoviruses showed that 91-orchid-1 shared 85.0∼96.1% nucleotide identity and 92.0∼97.5% amino acid identity with those of CaCV infecting tomato and capsicum in Australia (isolate 958;McMichael et al 2002), Thailand (isolate AIT) (Premachandra et al 2005), peanut in southern China (isolate CP; Chen et al 2007), Gloxinia tospovirus HT (accession No. AF059578;Hsu et al 2000) and Gloxinia ringspot virus (accession No.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the N gene sequences of the WSMoV serogroup of tospoviruses showed that 91-orchid-1 shared 85.0∼96.1% nucleotide identity and 92.0∼97.5% amino acid identity with those of CaCV infecting tomato and capsicum in Australia (isolate 958;McMichael et al 2002), Thailand (isolate AIT) (Premachandra et al 2005), peanut in southern China (isolate CP; Chen et al 2007), Gloxinia tospovirus HT (accession No. AF059578;Hsu et al 2000) and Gloxinia ringspot virus (accession No.…”
Section: Discussionmentioning
confidence: 99%
“…comm.). C. claratris has been shown to transmit CaCV in Thailand (Premachandra et al, 2005). These findings may indicate a Southeast Asian origin for CaCV.…”
Section: Capsicum Chlorosis Virus (Cacv)mentioning
confidence: 91%
“…claratris has recently been reported as a vector of Capsicum chlorosis virus (CaCV) in Thailand (Premachandra et al, 2005).…”
Section: Thrips Vectors Of Tospovirus Speciesmentioning
confidence: 99%
“…The order Thysanoptera is considered monophyletic based on morphological and molecular characteristics (Mound et al, 1980;Crespi et al, 1996). Presently, twelve thrips species are recognized as vectors transmitting tospoviruses (Bunyaviridae), including 16 virus species (Reddy et al, 1991;Yeh et al, 1992;Chen and Chiu, 1996;Mumford et al, 1996;Singh and Krishnareddy, 1996;Webb et al, 1997;Cortês et al, 1998;Gera et al, 1998;Bezerra et al, 1999;Kato et al, 1999;Nagata and de Ávila, 2000;Lee et al, 2002;Ullman et al, 2002;Nagata et al, 2004;Ghotbi et al, 2005;Lin et al, 2005;Premachandra et al, 2005;Ohnishi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%